AKTIVITAS ANTIBAKTERI FILTRAT Streptomyces sp. KCM2 TERHADAP MULTIDRUG RESISTANT Acinetobacter baumannii SECARA IN VITRO - LOSIANI, NI KADEK; KAWURI, RETNO; DARMADI, A. A. KETUT (Jurnal Biologi Udayana; Vol 21 No 1 (2017): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2017.vol21.i01.p05, 2017)
Acinetobacter baumannii is one of the pathogen which leads to multidrug resistant (MDR-A baumannii). This pathogen is often causing outbreaks of infections to the patients which are receiving treatment in the intensive care unit in hospital. This study aims to find out the antibacterial activity and the Minimum Inhibitory Concentration (MIC) of Streptomyces sp. KCM2 filtrate in inhibiting the growth of MDR-A baumannii. Streptomyces sp. KCM2 isolates was isolated in rhizosphere of white turmeric (Curcuma mango Val.) (Losiani et al., 2016). MDRA. baumannii isolates were obtained from stock culture in Clinical Microbiology Laboratory Sanglah Hospital in Denpasar. The antibacterial and the MIC test of Streptomyces sp. KCM2 filtrate was using the wells diffusion method. The research design was used Completely Randomized Design (CRD) and the inhibitory zone diameter data of MIC test were analyzed by Analysis of Varian (ANOVA), and then continued by Duncan Multiple Range Test in significance level 5%. The results of this study showed that the Streptomyces sp. KCM2 filtrate was able inhi biting with diameter zone of 23,44 mm and MIC of filtrate was 4% (v/v) with inhibition zone diameter of 8.77 mm.